Seroprevalence of Toxoplasma gondii in students with occupational risk - Troncoso Toro, Ignacio Eduardo.; Fischer Wiethuchter, Christof.; Cuevas H., Andrea.; Céspedes Cortes, Benjamín.; Valenzuela C., Adela.; Flores C., Yennifer.; Weinborn A., Romy.; Muñoz G., Paulina.; Arrué B., Kristofer.; Bustamante C., Catalina.; Dabanch P., Jeannette. (Sociedad Chilena de Infectología, 2022)
Background: Toxoplasmosis is a disease that results from infection with the Toxoplasma gondii parasite, one of the world›s most common parasites. The zoonotic infection usually occurs by eating undercooked contaminated meat or by contact with contaminated cat feces. A few studies of toxoplasmosis in healthy and immuno-compromised persons were done in Chile, but investigations related to occupational risk groups, such as Veterinary Medicine students were not studied. Aim: Determine the seroprevalence for T. gondii in Veterinary Medicine students at a university located in the center-south of the country, and evaluated to association with intrinsic variables. Methods: Peripheral blood samples were taken from 74 veterinary students from a university in south-central Chile. Immunoassay with sequential chemiluminescent was used as diagnostic technique. Results. Of the total number of students, 16 were seropositive, which is equivalent to 21.6%, the largest number of seropositive students was female (75%), they were in the age range between 24 and 26 years of age (43.7% ), all consumed meat and vegetables (100%) and collected pet cat feces without protection 50 (68,7%). Conclusions: The results obtained show the presence of antibodies against T. gondii in Veterinary Medicine students. To the authors’ knowledge, it is the first serological study for toxoplasmosis performed in university students of Veterinary Medicine in Chile.
Seroprevalencia de Toxoplasma gondii en estudiantes con riesgo ocupacional
Keywords: Antibody - Estudiantes; Toxoplasmosis; Medicina veterinaria; Zoonosis